Pulsed I–V Analysis of Slow Domain Switching in Ferroelectric Hf0.5Zr0.5O2 Using Graphene FETs - Hyeon Jun Hwang; Seung Mo Kim; Byoung Hun Lee (Advanced Electronic Materials, 2024)
Abstract In this study, the domain switching mechanism of ferroelectric HZO thin films is investigated by analyzing the bulk charge of a graphene field‐effect transistor with an HZO dielectric device by using a pulsed IV measurement method. The domain switching speed, which is generally difficult to observe from a typical DC‐IV analysis of metal‐oxide‐semiconductor field‐effect transistors using a parameter analyzer, is investigated via the fast pulsed IV analysis method. Based on the measurements, most of the ferroelectric HZO domains are fast switched within 100 ns; however, domains that require a longer switching time in the order of 1 ms are also identified. Short pulses can be continuously applied to minimize the influence of other domains that are not switched by the switched domain. The feasibility of partial switching of the domains, which can be utilized for the multi‐functional operation of ferroelectric HZO devices, is observed. The results suggest that further investigation of the physical properties of slow‐switching domains is necessary to develop future synaptic array applications.